2021
DOI: 10.3390/separations9010008
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Ecdysterone in Dietary Supplements and Spinach by Ultra-High-Performance Liquid Chromatography-Tandem Mass Spectrometry

Abstract: Ecdysterone is a naturally occurring steroid hormone of the ecdysteroid class. This group is widely marketed to athletes in dietary supplements as a “natural anabolic agent”, advertised to increase strength and muscle mass during resistance training, reduce fatigue and ease recovery. The aim of the study was to develop and validate a straightforward approach for identifying ecdysterone in dietary supplements by means of ultra-high-performance liquid chromatography–tandem mass spectrometry (UHPLC-MS/MS). Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10] Abnormally, Grucza et al have reported ecdysterone amount in fresh spinach as 0.1 µg g −1 f.w. [11] The levels of ecdysterone reported in spinach suggest that the normal amount of ecdysterone from spinach in a daily diet is rather low.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9][10] Abnormally, Grucza et al have reported ecdysterone amount in fresh spinach as 0.1 µg g −1 f.w. [11] The levels of ecdysterone reported in spinach suggest that the normal amount of ecdysterone from spinach in a daily diet is rather low.…”
Section: Introductionmentioning
confidence: 99%
“…Quinoa and spinach are two edible plants rich in ecdysterone in varying amounts (Bajkacz et al, 2020;Bakrim et al, 2008;Chen & Feng, 2021;Gorelick et al, 2020;Graf et al, 2014;Graf et al, 2016;Grebenok & Adler, 1991;Grucza et al, 2021;Kumpun et al, 2011). Since its inclusion in the WADA monitoring program (World Anti-Doping Agency, 2020), the urinary excretion of ecdysterone from food became a topic of interest.…”
Section: Discussionmentioning
confidence: 99%
“…Fresh, cooked, and frozen leaves of spinach also revealed a significant variation in the content of ecdysterone, 80 to 428 µg/g dry mass reported by Fang et al (Fang et al, 2022), 17 – 885 µg/g dry mass based on the study of Bajkacz (Bajkacz et al, 2020), and 24 µg/g as investigated by Chen et al (Chen & Feng, 2021). On the other hand, only a small amount of ecdysterone (0.1 µg/g FW) was quantified from fresh spinach as reported by Grucza et al (Grucza et al, 2021). The high variation in the content of ecdysterone in spinach is related to the location of the growing plants, the genetic information, the growing season, the development stage of plants, and plant variety (Bakrim et al, 2008; Gorelick et al, 2020; Grebenok & Adler, 1991).…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, 20-hydroxyecdysterone is usually marked as "natural anabolic agent" [27]. Although many researchers suggest that ecdysterone supplementation has been used by Soviet athletes since the 1980s and it was sometimes called the "Russian secret" (R. carthamoides naturally grows in Russia), nowadays supplementation with R. carthamoides and other products containing ecdysterone is common practice among athletes from all over the world, because of the high adaptogenic potential of the molecule [8,18,[27][28][29]. The intake of R. carthamoides extracts and its contained secondary metabolites, ecdysterone, and turkesterone, has been associated with multiple athletic performance benefits [30][31][32][33], as shown in Figure 2.…”
Section: Introductionmentioning
confidence: 99%